Analysis of Human Resource Competency as Effort to Increase SMEs Economic Sector Productivity with Gender as Differentiating Variable - Dian Prihardini Wibawa (Integrated Journal of Business and Economics (IJBE), 2018)
Competency is a very important factor in increasing work productivity. A qualified workforce will have a positive impact on improving business productivity. Thus, the level of corporate profitability also increased. Human resource improvement strategy is an excellent strategy apart from other factors such as technology improves. Increased strategy through human resource competence can be done with the improvement of ability, attitude, knowledge, and expertise. The purpose of this research is to see the influence of human resource competence on the productivity of small and medium business actors with gender variable as differentiator variable in Pangkalpinang city. The result of this research indicates the male labor variable of competency which influence productivity is only knowledge variable, while other variables have no effect. While for women the ability variable, skill and knowledge have an effect on to productivity.